PENGARUH LATIHAN LADDER DRILL TERHADAP KELINCAHAN MENGGIRING BOLA PADA PEMAIN DI CLUB SEPAK BOLA GUNTOR BERASTAGI USIA 13-15 TAHUN - Bambang Sihombing; Janwar Firhasan Sinuraya; Tri Widia Astuti Tamba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of ladder drill training on dribbling agility among soccer players aged 13–15 years at Guntor Berastagi Club. The background of this research is based on the low level of players’ agility in changing direction and controlling the ball quickly during training and matches. This research used a quantitative approach with an experimental method and a One Group Pretest-Posttest design. The sample consisted of 19 players selected using a saturated sampling technique. Data were collected through dribbling agility tests conducted before (pretest) and after (posttest) the ladder drill training. Data analysis was performed using the Shapiro-Wilk normality test and hypothesis testing with a paired sample t-test. The results showed that the average pretest time was 7.36 seconds, while the posttest was 6.05 seconds, indicating an improvement in agility. The hypothesis test showed a significance value of 0.01 (p < 0.05), meaning that ladder drill training had a significant effect on dribbling agility. It can be concluded that ladder drill training is effective in improving dribbling agility in youth soccer players and can be applied as an appropriate training method in sports coaching programs.